Effect of Date Fruit Consumption on Hemoglobin Levels in Anemic Adolescent Girls - Indryani; Mustar; Hasnidar; Pattola; Alda Anggraini (The Indonesian Institute of Science and Technology Research, 2026)
Anemia among adolescent girls remains a persistent public health problem, particularly in low- and middle-income countries, where increased nutritional requirements and menstrual blood loss elevate the risk of iron deficiency. Although iron supplementation is the primary preventive strategy, low adherence among adolescents necessitates complementary approaches. This study aimed to evaluate the effect of date fruit consumption on hemoglobin levels among anemic adolescent girls. A quantitative pre-experimental study with a one-group pretest–posttest design was conducted in a school setting in South Sulawesi, Indonesia. Hemoglobin screening was performed on 70 adolescent girls, and 10 anemic participants were selected using purposive sampling. The intervention consisted of consuming 100 g of date fruit (approximately 7–8 fruits) daily for seven consecutive days. Hemoglobin levels were measured before and after the intervention using a portable hemoglobin analyzer. Data were analyzed using descriptive statistics and the Wilcoxon Signed-Rank Test, with statistical significance set at p < 0.05. Mean hemoglobin levels increased significantly from 11.09 g/dL at baseline to 13.38 g/dL after the intervention, with an average increase of 2.29 g/dL (p = 0.005). These findings suggest that short-term date fruit consumption significantly improves hemoglobin levels among anemic adolescent girls. In conclusion, date fruit represents a feasible, culturally acceptable, food-based nutraceutical intervention that may complement existing anemia prevention programs. Further randomized controlled studies with larger samples and longer follow-up are recommended to confirm these findings and evaluate their long-term effectiveness.